FINANCIAL INSTRUMENTS OF ANTI-CRISIS MANAGEMENT IN THE DIGITAL AGE - Gudz , Olena; Petkun , Svitlana (Public Management and Policy, 2026)
The article clarifies the essence, features and tasks of anti-crisis management, which made it possible to substantiate that its financial instruments in the digital age are becoming a key factor in ensuring the stability and development of organizations and institutions. Their effectiveness is determined by the ability to combine traditional financial stabilization mechanisms with innovative digital solutions that provide speed, transparency and adaptability in crises. Modern trends in the use of financial instruments of anti-crisis management in Ukraine during the war period and factors influencing these processes are identified. In conditions of military and global challenges, Ukrainian organizations and institutions demonstrate a tendency to actively use digital platforms, blockchain technologies, crowdfunding tools and risk forecasting systems. This allows not only to maintain liquidity and minimize losses, but also to open up new opportunities for attracting capital, increasing investor confidence and integration into international financial markets. At the same time, problems associated with limited access to financial resources, high risks and insufficient adaptation of the legal environment are revealed. Overcoming them requires a comprehensive approach: developing financial literacy, improving the regulatory framework, strengthening cybersecurity and expanding state support for business. The introduction of the proposed modern financial instruments into the anti-crisis management system opens up a new level of stability, transparency and competitiveness for organizations and institutions. It is summarized that anti-crisis management in the digital age is transformed into a strategic tool not only for survival and resilience, but also for the long-term development of organizations and institutions. The use of modern financial technologies in combination with classical tools creates a new paradigm of anti-crisis management, which is able to ensure economic sustainability, financial stability, competitiveness and integration of Ukraine into the global financial ecosystem.